Prevention of Stunting and TB in Banjarejo Village, Panekan District, Magetan Regency through Preventive Health Education Content - Zahra, Almira Althaf; Nuraena, Binawan Kerti; zondia, Fidelma Azzahra Pingkan; Nadia, Ahsanu; Sutopo, Sherina Widya Kusumaning; Kusumaningtyas, Nisrina Triwulan; Zihni, Fakhirin; Putri, RR. Diandri Rahmantya (Lembaga Penelitian dan Pendidikan Mandala, 2024)
One of the problems of toddler growth in Indonesia is stunting. Stunting is caused by various factors, such as the condition of the pregnant mother, nutritional intake in infants and toddlers, economic conditions and the condition of the toddlers themselves. The stunting prevalence in Magelang district in 2021 was 17.2%. This is still quite high because it is not in accordance with the 2024 RPJMN, which is < 14%. This study will try to discuss efforts to prevent stunting and tuberculosis through preventive health education. The results show that through preventive health education, there is a growing understanding that the pengetuan ibi greatly contributes to the prevention and handling of stunting. Through this method, a good network is expected to grow in stunting prevention, including family support, children's physical health, nutritional status and contributive home environment conditions. This is productively expected to be able to prevent and handle stunting and TB cases more comprehensively.